Peran Bhabinkamtibmas dalam Penanggulangan Narkoba Di Kecamatan Bukit Raya (Studi Kasus Unit Binmas Polsek Bukit Raya Polresta Pekanbaru) - Kristiady, Dedy; Fakhri Usmita (Sisi Lain Realita, 2024)
ABSTRACT Drug abuse in the city of Pekanbaru has increased significantly in recent years. The police, through the Bhabinkamtibmas Unit, have made many efforts to eradicate this drug problem. However, new challenges continue to emerge along with technological developments and the social dynamics of society. With a better understanding of the dynamics of drug control at the regional level, it is hoped that specific policy recommendations and innovative solutions will emerge to overcome drug-related challenges in Pekanbaru City, especially in Bukit Raya District. The results of this research are descriptive data to explain the phenomena encountered based on the researcher's observations. Based on the research results, it is known that the handling of drug trafficking crimes carried out by the Air Dingin and Simpang Tiga Bhabinkamtibmas involves going directly to the community. Bhabinkamtibmas has a preventive role in the prevention of drug trafficking by conducting regular outreach to the community. Based on the crime prevention theory, there are two types of prevention carried out by Bhabinkamtibmas in Air Dingin and Simpang Tiga Subdistricts, namely: (1) primary prevention, such as implementing a door-to-door system to find out what the community's problems are while establishing good communication between Bhabinkamtibmas and the community. (2) secondary prevention, such as arresting perpetrators who commit crimes.